Childhood cancer survivorship care: A qualitative study of healthcare providers’ professional preferences - McLoone, Jordana K.; Chen, Weihan; Wakefield, Claire E.; Johnston, Karen; Bell, Rachael; Thornton-Benko, Elysia; Cohn, Richard J.; Signorelli, Christina (Frontiers in Oncology, 2022)
Purpose: Childhood cancer survivorship care is a complex specialty, though it is increasingly being integrated into the general practitioner’s (GP) remit. Establishing the essential components of tertiary- and primary-led care, to maximize the benefits and overcome the challenges inherent to each, is essential to inform the development of survivor-centered, sustainable care models. Methods: We used the qualitative principles of semi-structured interviewing, verbatim transcription, coding (supported by NVivo12) and thematic analysis, to collect and evaluate the views and preferences of pediatric oncologists, survivorship nurse coordinators, and GPs currently caring for childhood cancer survivors. Results: Seventy healthcare providers (19 oncology staff and 51 GPs) from 11 tertiary hospitals and 51 primary practices across Australia and New Zealand participated. Participants reported specialist expertise and holistic family-centered care as the key benefits of tertiary and primary care respectively. Participants reported that tertiary-led survivorship care was significantly challenged by a lack of dedicated funding and costs/travel burden incurred by the survivor, whereas primary-led survivorship care was challenged by insufficient GP training and GPs’ reliance on oncologist-developed action plans to deliver guideline-based care. GPs also reported a need for ongoing access to survivorship expertise/consultants to support care decisions at critical times. The discharge of survivors into primary care limited late-effects data collection and the rapid implementation of novel research findings. Conclusions: Healthcare professionals report that while a risk-stratified, collaborative model of survivor-centered care is optimal, to be implemented successfully, greater provisions for the ongoing engagement of GPs and further access to GP education/training are needed.